#### Answer

x$^2$+2x-16

#### Work Step by Step

(4x$^2$+2x-7)-(3x$^2$+9)
=4x$^2$+2x-7-3x$^2$-9
=x$^2$+2x-16

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

x$^2$+2x-16

(4x$^2$+2x-7)-(3x$^2$+9)
=4x$^2$+2x-7-3x$^2$-9
=x$^2$+2x-16

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.